STUDI KELAYAKAN PLTM CIATEN KABUPATEN BOGOR DARI SEGI HIDROLOGI DAN EKONOMI - Susilo, Adhi; wahyudi, Slamet Imam; Niam, Moh Faiqun (Pondasi, 2024)
Rivers are one of the important water sources for life on earth. Both humans,animals and plants, all need water to maintain life. Rivers flow from upstream todownstream, moving from high places to low places. Microhydro, or MicrohydroPower Plant (PLTM), is a small-scale power plant that uses water power as itsdriving force, such as irrigation canals, rivers or natural waterfalls, by utilizing theheight of the waterfall (head) and the amount of water discharge. The Cianten Riverhas sufficient water potential throughout the year, reliable discharge, suitablecontours, and has been utilized for PLTM.Data collection techniques in this research include observation and data collectionin the field by observing and recording data on the area of each watershed and thearea of civil building planning. Several models used for hydrological analysis are theTank Model, FJ Mock Model, and Markov Lag 1 Model. Apart from that,researchers also carried out financial evaluations of Microhydro Power Plants(PLTM).The results obtained for the Cianten I PLTM scheme/layout include the dam andintake building, sand trap, waterway, headpond, penstock, powerhouse, and exhaustchannels (tailrace). The generation discharge that can be selected based on the plantfactor value is in the probability range of 35% - 55%. The Cianten I PLTM project isconsidered feasible to be realized if it is in a condition of normal value andincreasing benefits. Under normal conditions, financial analysis and sensitivityanalysis show the Project FIRR results are 9.88%, FIRR on Equity is 36.52%, NPVis IDR. 2,916,937,135, and a BCR of 1.03 with an investment payback period of10.87 years.